PENGARUH PROMOSI, KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN KONSUMEN GOJEK (Studi Kasus Ini Di Wilayah Kelurahan Cipinang Besar Utara) - Desy Amaliati Setiawan; Irfa Arif Husen; Rahmat Yuliansyah; Said Khaaerul Wasif (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to find out (1) how much the influence of promotion on gojek consumer satisfaction in Cipinang Besar Utara. (2) how much influence of service quality on gojek consumer satisfaction in Cipinang Besar Utara, (3) how much influence of customer value on gojek consumer satisfaction in Cipinang Besar Utara, and (4) how much influence of promotion, quality of service, customer value on gojek consumer satisfaction in Cipinang Besar Utara. This study used primary data with the dissemination of questionnaires and analysis of respondents' answers. The population of this research is the people who use gojek services in the big Cipinang Besar Utara. The sample in this study amounted to 100 respondents using purposive sampling. The analysis methods used are validity test, reliability test, partial and multiple determination coefficient analysis, and hypothesis testing. The results showed that the promotion was partially influential but not significant with a contribution of 7.34% in influencing Gojek consumer satisfaction in the Cipinang Besar Utara area. Partial service quality has a significant effect with a contribution of 33.40% in influencing Gojek customer satisfaction in the Cipinang Besar Utara area. Partial customer value has a significant effect with a contribution of 52.27% in influencing Gojek customer satisfaction in the Cipinang Besar Utara area. And then simultaneously the promotion, quality of service, customer value have a significant effect on Gojek customer satisfaction in the Cipinang Besar Utara area with a contribution of 57.76%.